Need help from an expert?
The world’s top online tutoring provider trusted by students, parents, and schools globally.
The intercepts of \( y = 2x^2 - 3x + 1 \) are the y-intercept at (0, 1) and the x-intercepts at (1, 0) and (0.5, 0).
To find the y-intercept, we set \( x = 0 \) and solve for \( y \). Substituting \( x = 0 \) into the equation \( y = 2x^2 - 3x + 1 \), we get:
\[ y = 2(0)^2 - 3(0) + 1 = 1 \]
So, the y-intercept is at the point (0, 1).
Next, to find the x-intercepts, we set \( y = 0 \) and solve for \( x \). This means we need to solve the quadratic equation:
\[ 2x^2 - 3x + 1 = 0 \]
We can use the quadratic formula \( x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \), where \( a = 2 \), \( b = -3 \), and \( c = 1 \). Substituting these values in, we get:
\[ x = \frac{-(-3) \pm \sqrt{(-3)^2 - 4(2)(1)}}{2(2)} \]
\[ x = \frac{3 \pm \sqrt{9 - 8}}{4} \]
\[ x = \frac{3 \pm 1}{4} \]
This gives us two solutions:
\[ x = \frac{3 + 1}{4} = 1 \]
\[ x = \frac{3 - 1}{4} = 0.5 \]
So, the x-intercepts are at the points (1, 0) and (0.5, 0).
In summary, the y-intercept is where the graph crosses the y-axis, and the x-intercepts are where the graph crosses the x-axis. For the quadratic equation \( y = 2x^2 - 3x + 1 \), these intercepts are (0, 1), (1, 0), and (0.5, 0) respectively.
Study and Practice for Free
Trusted by 100,000+ Students Worldwide
Achieve Top Grades in your Exams with our Free Resources.
Practice Questions, Study Notes, and Past Exam Papers for all Subjects!
The world’s top online tutoring provider trusted by students, parents, and schools globally.